Peran Fintech Syariah dalam Meningkatkan Kinerja Keuangan UMKM Di Masa Pandemi Covid-19 - Belinda Nurfadila; Dina Sabilatun Najah; Agus Maulana (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2022)
This article aims to explain the role of Sharia Fintech in order to improve the financial performance of SME. This article uses literature study method by looking for references from several sources that are relevant to the topic. Researchers found that Sharia Fintech has a role in making it easier for SME  to get capital loans in an easy way and in accordance with Islamic law. During the Covid-19 pandemic like today, Sharia Fintech has a more role for SME. Apart from being a provider of capital loans, Sharia Fintech can also be used in the transaction process and financial management of SME. So that the financial performance of SME will be faster, easier, more efficient, and of course in accordance with the provisions and Islamic law.